The adversity on establishing places of worship: has religious freedom failed in Indonesia? - Ridwan Arifin; Hanif Helmi; Ngaboawaji Daniel Nte; Waspiah Waspiah; Dian Latifiani (Faculty of Law, University of Muhammadiyah Malang, 2021)
Religious freedom has various interpretations in practice, although the rule of law regulates this right. In many cases, freedom of religion is closely related to human rights and security studies, however, not infrequently, the cases intersect with political policies. This paper aims to analyze various cases regarding religious freedom in Indonesia concerning human rights. This paper examines various phenomena related to difficulties and establishing places of worship, especially for certain groups in Indonesia in various policies and legal regulations in Indonesia. The method used for this research is non-empirical research. All data dan information analyzed come up from various previous research. This paper found and underlined that debates on the relativity of human rights often lead to different perceptions in human rights standards. Various laws relating to communities of places of worship, in many cases and considered by many experts to violate the basic principles of human rights. This paper also emphasized that the fulfillment of human rights in Indonesia concerning religious freedom cannot be separated from historical, sociological, and cultural factors of the Indonesian people themselves.